DAYA TERIMA BROWNIES KUKUS DENGAN PENAMBAHAN KULIT PISANG RAJA (Musa paradisiaca L. varsapientum) - Manjilala Manjilala; Zakaria Zakaria; Erida Nurizza (Media Gizi Pangan, 2022)
Calcium is one of the important nutrients for pregnant women, lack of calcium during pregnancy will have an impact on fetal development during pregnancy. Calcium intake of pregnant women in some developing countries is low.This study aims to determine the acceptability and calcium content of steamed brownies with the addition of plantain peel puree. This type of research is Post Test Group Design, panelists are 30 people. The acceptability data was tabulated in a table and then analyzed using the fridmen test. The data is presented in the form of a table accompanied by a narration.The results of this study indicate that the panelists' acceptance of Brownies with the addition of plantain peel from the aspect of color, aroma, texture, and taste is the most preferred formula F2 with a concentration of 20%:80%. It is recommended that further researchers need to test the protein content and water content and develop Brownies products using local ingredients with high nutritional value.